Improved hydrogen production using lead-free and air stable perovskite-like Cs3Sb2I9 - Ahmad, Khursheed; Raza, Waseem; Alsulmi, Ali; Kim, Haekyoung (Materials Chemistry and Physics, 2023)
In previous years, lead (Pb) free all-inorganic perovskite like materials have been widely used for photovoltaic applications. Herein, we have fabricated cesium antimony iodide (Cs3Sb2I9) perovskite like-material by simple and effective approach. Further, phase and purity of Cs3Sb2I9 perovskite like material was confirmed by XRD. The structural surface of Cs3Sb2I9 perovskite like material was checked by SEM. The elemental composition of Cs3Sb2I9 perovskite like material was determined by XPS. Further, we have investigated the photo-catalytic properties of Cs3Sb2I9 perovskite like material for hydrogen production application. Cs3Sb2I9 showed hydrogen generation of 95.54 μmol g−1. Platinum was used as bi-catalyst and obtained results for Cs3Sb2I9/Pt (2 mg) showed excellent hydrogen generation of 804.54 μmol g−1 with decent stability up to 50 h.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Cs; H; Pb free; Photo-catalysis